Towards ultrasensitive malaria diagnosis using surface enhanced Raman spectroscopy - Chen, Keren (2018)
We report two methods of surface enhanced Raman spectroscopy (SERS) for hemozoin detection in malaria infected human blood. In the first method, silver nanoparticles were synthesized separately and then mixed with lysed blood; while in the second method, silver nanoparticles were synthesized directly inside the parasites of Plasmodium falciparum. It was observed that the first method yields a smaller variation in SERS measurements and stronger correlation between the estimated contribution of hemozoin and the parasitemia level, which is preferred for the quantification of the parasitemia level. In contrast, the second method yields a higher sensitivity to a low parasitemia level thus could be more effective in the early malaria diagnosis to determine whether a given blood sample is positive.